2020
DOI: 10.3920/cep190047
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of, and relationship between, distal limb and facial asymmetry, and performance in the event horse

Abstract: Identification of influential conformational traits is an important aspect in choosing the most appropriate horse for a specific discipline with regards to both performance potential and career longevity. Symmetry of bilateral traits, both functional and non-functional, demonstrates the ability of an individual to display their genotypic quality through their phenotype. External trait symmetry has been linked to effective functioning and health of a number of internal organ systems. The identification of a rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…Horses worldwide are typically handled from their left (‘near’) side and many racehorses do fast track work in one direction only (clockwise in Hong Kong), but limb asymmetry also exists in horses not performing single‐direction training. 25 , 26 Previous studies have reported significant differences between right and left limbs; for example, difference in length between right and left third metacarpal bone from Thoroughbred racehorses in Victoria and South Australia 27 ; five postmortem measurements were larger in the left femur compared to the right femur from Thoroughbred racehorses in New South Wales, Australia. 28 Images were supplied individually in random order and not as single‐animal sets or left–right pairs, so direct within‐individual comparisons were not available to the model to use in laterality discrimination.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Horses worldwide are typically handled from their left (‘near’) side and many racehorses do fast track work in one direction only (clockwise in Hong Kong), but limb asymmetry also exists in horses not performing single‐direction training. 25 , 26 Previous studies have reported significant differences between right and left limbs; for example, difference in length between right and left third metacarpal bone from Thoroughbred racehorses in Victoria and South Australia 27 ; five postmortem measurements were larger in the left femur compared to the right femur from Thoroughbred racehorses in New South Wales, Australia. 28 Images were supplied individually in random order and not as single‐animal sets or left–right pairs, so direct within‐individual comparisons were not available to the model to use in laterality discrimination.…”
Section: Discussionmentioning
confidence: 97%
“…While size may be a contributing factor, yet others such as length–width aspect ratio, cortical thickness or opacity, or trabecular bone texture might also contribute to the model weights. Individual horses commonly have bone dimensions that are asymmetric in the opposite direction to mean population‐level asymmetry, 25 , 26 which may help to account for our model's imperfect accuracy in laterality classification.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation